DADE HAMILTON’S CHARACTER DEVELOPMENT AS AN OPEN HOMOSEXUAL IN NICK BURD’S THE VAST FIELDS OF ORDINARY - AGUSTINA, ERMY DYAH AYU (Jurnal Ilmiah Mahasiswa FIB, 2014)
Agustina, Ermy Dyah Ayu. 2013. Dade Hamilton’s Character Development as an Open Homosexual in Nick Burd’s  The Vast Fields of Ordinary. Study Program of English, Universitas Brawijaya. Supervisor: Dyah Eko Hapsari. Co-supervisor: Aris Siswanti.Keyword: character development, homosexuality, social psychology.Homosexuals are a part of a minor community referred as LGBT (Lesbian, Gay, Bisexual and Transgender). They are discriminated and physically and verbally oppressed because of their abnormal sexual behaviors. These cause a negative impact on the LGBT teenagers for they become too afraid to reveal their true identities. The Vast Fields of Ordinary depicts the life of a teenager named Dade Hamilton and his development as a homosexual and how  he deals with identity crisis. This study aims at finding the roles of external factors that influence Dade’s character development.      Social psychology approach is used to analyze the external factors that influence Dade’s thought and behavior. Interpersonal relationship, group dynamics, and identity development theories are used to support the analysis. Theories regarding homosexuality in a social psychology context are used to examine his identity development as a homosexual and how the status affects his social life.   The results of this study  reveals that there are four factors that influence Dade’s character development: peers, family, lover and group. They give positive influences to his traits and help him to be more mature and overcome his identity crisis. As a result, he can finally reveal his true identity and live as an open homosexual.    The writer suggests English Department students to do a research on LGBT-themed literature using either Cass Identity Model that describes the stages of lesbian/gay identity development or Fassinger’s theory that explores the two processes and four phases of gay identity development.  She hopes that doing this study can raise the awareness of the existence of LGBT people in society and decrease the level of discrimination against them.